Is the death penalty dying? European and American perspectives - Martschukat, Jürgen (Cambridge University Press, 2011)
Is the Death Penalty Dying? provides a careful analysis of the historical and political conditions that shaped death penalty practice on both sides of the Atlantic from the end of World War II to the twenty-first century. This book examines and assesses what the United States can learn from the European experience with capital punishment, especially the trajectory of abolition in different European nations. As a comparative sociology and history of the present, the book seeks to illuminate the way death penalty systems and their dissolution work, by means of eleven chapters written by an interdisciplinary group of authors from the United States and Europe. This work will help readers see how close the United States is to ending capital punishment and some of the cultural and institutional barriers that stand in the way of abolition. Yet, more than that, this book shows how the death penalty has helped define the political and cultural identities of both Europe and the United States.